PENGARUH STRATEGI MEDIA PROMOSI OFFLINE,DAN DIGITAL, SERTA EVENT MARKETING DALAM MENARIK MINAT PENGUNJUNG PLAZA KALIBATA - Akhdan Nur Firman, (2023)
Plaza Kalibata is a shopping center in the South Jakarta area. In general, shopping centers or commonly called malls have a strategy to attract visitors. Plaza Kalibata has its own marketing strategy steps to attract shopping visitors, so a problem formulation is formulated according to this research, namely whether offline and digital promotional media strategies, as well as event marketing have an effect on attracting visitors. The purpose of this research is to find out, prove and analyze whether offline and digital promotional media strategies, as well as event marketing have an effect on attracting visitor interest. The population in this research were all visitors or people who had visited Plaza Kalibata. The sample used was 150 visitors. Using the Partial Least Square (PLS) analysis technique with SmartPLS 3.2.9 software. The results obtained show that the variables of offline and digital promotional media, as well as event marketing have a positive and significant influence in attracting the interest of Kalibata Plaza visitors. Keywords: offline promotional media, digital promotional media, event marketing, visitor interest